Collagen-associated syntropy in children with functional disorders of the digestive system - Stoieva, T. V.; Dzhagiashvili, O. V.; Prokhorova, S. V.; Gudz, V. A.; Yemelyanova, O. Yu. (Zaporozhye Medical Journal, 2018)
Objective. The aim of this study was to determine the features of collagen-associated syntropic pathology in children with functional gastrointestinal disorders. Materials and methods. 63 children with functional gastrointestinal disorders aged 2.5 to 16 years were examined. Two clinical groups of patients depending on the leading clinical manifestations were identified: children with irritable bowel syndrome – 39 patients (61.9 %) and children with functional disorders of the biliary tract – 24 (38.1 %) of patients. All children, except for the general clinical examination, were evaluated for individual phenotypic signs of connective tissue dysplasia using diagnostic criteria for the severity of connective tissue dysplasia by L. N. Abbakumova, and collagen type III alpha 1 polymorphism (rs1800255 2092G>A) by PCR-RFLP (restriction fragment length polymorphism) method was determined. Results. Digestive system syntropic pathology was defined in 84.13 % (95 % CI 74.93 – 93.33) of the examined patients. A statistically significant association was found between the frequency of gallbladder anomalies (χ2 = 8.75; P = 0.003), pancreas exocrine function violation (χ2 = 8.97, P = 0.003), metabolic disturbances presence in the form of secondary acetonemic syndrome (χ2 = 8.5; P = 0.001) and functional disorders of the biliary tract. The severity of connective tissue dysplasia in preschool children was characterized by mild and moderate manifestations (OR = 4.27 (95 % CI 1.32 – 13.82; P = 0.025)), there were severe manifestations of dysplasia in the older children group (OR = 0.23 (95 % CI 0.07 – 0.76, P = 0.025)). By the results of molecular-genetic test the most of children – 47.62 % (95 % CI 35.04 – 60.2) were genotyped for heterozygous rs1800255, COL3A1 G/A polymorphism, with significant prevalence of patients with the biliary tract functional disorders group (P = 0.008), which associated with wide range of accompanying pathology (P = 0.002) and severe dysplastic signs (P = 0.034). Conclusions. The wide prevalence of the syntropic pathology in children with functional gastrointestinal disorders has been determined. Genetic polymorphism with predominance of the G/A genotype has been revealed. The statistically significant correlation of the G/A genotype with severe phenotypic signs of connective tissue dysplasia has been shown. The association of genetic polymorphism with age and functional disorders of the biliary tract has been established.